Soil Bacterial Community Response and Nitrogen Cycling Variations Associated with Subalpine Meadow Degradation on the Loess Plateau, China - Luo, Zhengming (Appl Environ Microbiol, 2020)
Grassland degradation is an ecological problem worldwide. This study aimed to reveal the patterns of the variations in bacterial diversity and community structure and in nitrogen cycling functional genes along a subalpine meadow degradation gradient on the Loess Plateau, China. Meadow degradation had a significant effect on the beta diversity of soil bacterial communities (P < 0.05) but not on the alpha diversity (P > 0.05). Nonmetric multidimensional scaling (NMDS) and analysis of similarity (ANOSIM) indicated that the compositions of bacterial and plant communities changed remarkably with increasing meadow degradation (all P < 0.05). The beta diversities of the plant and soil bacterial communities were significantly correlated (P < 0.05), while their alpha diversities were weakly correlated (P > 0.05) along the meadow degradation gradient. Redundancy analysis (RDA) showed that the structure of the bacterial community was strongly correlated with total nitrogen (TN), nitrate nitrogen (NO(3)(−)-N), plant Shannon diversity, plant coverage, and soil bulk density (all P < 0.05). Moreover, the abundances of N fixation and denitrification genes of the bacterial community decreased along the degradation gradient, but the abundance of nitrification genes increased along the gradient. The structure of the set of N cycling genes present at each site was more sensitive to subalpine meadow degradation than the structure of the total bacterial community. Our findings revealed compositional shifts in the plant and bacterial communities and in the abundances of key N cycling genes as well as the potential drivers of these shifts under different degrees of subalpine meadow degradation. IMPORTANCE Soil microbes play a crucial role in the biogeochemical cycles of grassland ecosystems, yet information on how their community structure and functional characteristics change with subalpine meadow degradation is scarce. In this study, we evaluated the changes in bacterial community structure and nitrogen functional genes in degraded meadow soils. Meadow degradation had a significant effect on bacterial community composition. Soil total nitrogen was the best predictor of bacterial community structure. The beta diversities of the plant and soil bacterial communities were significantly correlated, while their alpha diversities were only weakly correlated. Meadow degradation decreased the potential for nitrogen fixation and denitrification but increased the potential for nitrification. These results have implications for the restoration and reconstruction of subalpine meadow ecosystem on the Loess Plateau.